The Strata Housing Attributes for Elderly to Age In Place - Amalina Azmi,; Peter Aning Tedong,; Zafirah Al Sadat Zyed, (2025)
As we navigate the journey of life, we encounter myriad experiences that shape who we are. Each stage brings new challenges and triumphs, and the process of ageing is no different. Ageing in place has becoming a popular trend among the elderly whereby they insist on growing older in a familiar place especially at their own house. Despite of their impairments, they prefer to ageing in place. Added to that, in line with the rapid urbanisation, they might ageing in place in a highrise building such as condominiums and apartments. However, this trend has triggered concerns among family members, such as, how safe are their parents or grandparents in their own homes?Thus, this book will delve into the high-rise building attributes that enable the elderly to age in place. Surveys and interviews were conducted among elderly individuals with impairments to gather input on the required high rise building attributes for them to age in place. Throughout the pages of this book, you will encounter diverse perspectives and experiences that illuminate the many-sided nature of ageing in place which contributes to 3 types of high-rise building attributes which are internal attributes, external attributes, and technology attributes. Together, we can create a nation that allows everyone to age gracefully, independently, and safely in either condominiums or apartments. May this book inspire us to envision and build a future where ageing in place in either condominiums or apartments is not only a possibility but a cherished reality for all.